1996
DOI: 10.1111/j.1472-765x.1996.tb00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Galacto-oligosaccharide production from lactose by Sirobasidium magnum CBS6803

Abstract: Galacto-oligosaccharide (Gal-OS) was produced from lactose by a yeast, Sirobasidium magnum CBS6803. With toluene-treated resting cells, 136 mg ml-1 of Gal-OS was produced from 360 mg ml-1 of lactose at 50 degrees C for 42 h. Then, the yield of Gal-OS was increased by a culture method in which cell growth followed the enzymatic reaction: 224 mg ml-1 of Gal-OS was produced at 30 degrees C for 60 h. Finally, combination of the toluene-treated resting cells and glucose oxidase plus catalase was applied to improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 6 publications
1
19
0
3
Order By: Relevance
“…The trisaccharide produced by ␤-galactosidase from B. bifidum was also identified as 3Ј-galactosyl-lactose (11). However, 4Ј-galactosyl-lactose and 6Ј-galactosyl-lactose were reported to be preferentially formed during the transgalactosylation reactions (1,39,40,62), and several ␤-galactosidases were found to produce more than one type of GaOS (1,57,62). Comparing the prebiotic effects of 3Ј-galactosyl-lactose, 4Ј-galactosyl-lactose, and 6Ј-galactosyl-lactose is essential to determine their relative values as nutraceutical additives for humans or animals.…”
Section: Discussionmentioning
confidence: 99%
“…The trisaccharide produced by ␤-galactosidase from B. bifidum was also identified as 3Ј-galactosyl-lactose (11). However, 4Ј-galactosyl-lactose and 6Ј-galactosyl-lactose were reported to be preferentially formed during the transgalactosylation reactions (1,39,40,62), and several ␤-galactosidases were found to produce more than one type of GaOS (1,57,62). Comparing the prebiotic effects of 3Ј-galactosyl-lactose, 4Ј-galactosyl-lactose, and 6Ј-galactosyl-lactose is essential to determine their relative values as nutraceutical additives for humans or animals.…”
Section: Discussionmentioning
confidence: 99%
“…Galacto-oligosaccharides, including the oligogalactosylated glucoses, are claimed to be beneficial for human health because they seem to promote the growth of bifidobacteria in the large intestine [1]. Several studies suggest that the volatile fatty acids resulting from the fermentation of galacto-oligosaccharides by the intestinal microflora improve the absorption ability of the intestinal epithelium [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Various parameters such as source of the enzyme, substrate concentration, pH, and temperature can influence the transgalactosylation and thereby the final yields of the different compounds formed [5]. The structures of oligogalactosylated glucoses reported so far range from dimers to pentamers [1,[6][7][8][9]. Depending on the biological origin of the b-galactosidase applied, different linkages be- Branched Glc residues also occur, whereas the oligogalactose fragments contain mainly (1 4) or (1 6) linkages.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Because of this, a number of studies have reported attempts to isolate a -galactosidase with high transgalactosylation activity from various microorganisms, [4][5][6][7][8] including Bacillus circulans, 12,13) Bifidobacterium adolescentis, 14) Lactobacillus reuteri, 15,16) and others. [17][18][19][20] Furthermore, the genes that encode -galactosidases from bacteria, including B. circulans, 21) Bifidobacterium bifidum [22][23][24][25] / Bifidobacterium infantis, 22,[26][27][28] L. reuteri, 29) L. plantarum, 30) and others, 20,31) have been cloned and sequenced, and the enzymes have been overexpressed in heterologous cells.…”
mentioning
confidence: 99%